Kualitas Hidup Pasien Artritis Reumatoid dan Faktor-Faktor Yang Memengaruhi - Rudy Hidayat; Nur Asicha; Dicky Levenus Tahapary; Suryo Anggoro Kusumo Wibowo (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2023)
Introduction: Rheumatoid arthritis (RA) is a rheumatic disease that often results in functional disability and decreased health-related quality of life (HRQoL). This study aims to evaluate the HRQoL and related factors in patients with RA.Method: This study enrolled 152 patients from Rheumatology polyclinic at RSUPN Dr. Cipto Mangunkusumo Jakarta. Sosiodemographic, clinical, and laboratory data related to disease activity, functional status, psychological problems, and number of comorbidities were collected. Disease activity was assessed with cumulative Disease Activity Score-28 with erythrocyte sedimentation rate (DAS28 ESR) for the last 6 months. HRQoL was assessed using the Indonesian EuroQol five-dimensional questionnaire (EQ-5D) and EQ global health visual analogue scale (VAS). Univariate analysis, bivariate and multivariate analysis were employed to identify factors related to HRQoL.Result: Of the enrolled participants, 90.8% were female with a mean age of 49.41 ± 12.31 years. Majority of subjects had moderate disease activity and an independent functional status. Median duration of illness was 3 (0 – 34) years. The study also identified psychological disorders such as anxiety (11.2%) and depression (20.4%). The median EQ-5D index value was 0.84 (0.170 – 1.000), and the median EQ VAS was 70 (40 – 100). Functional disability, disease activity, and depression were independently associated with both the index EQ-5D score and EQ VAS, while anxiety and number of comorbidities were only independently associated with EQ VAS.Conclusion: Functional disability, disease activity, psychological disorders and number of comorbidities negatively impact the HRQoL of RA patients. Hence, evaluation of these factors should be considered in the standard of care for RA patients.